A NOVEL RP-HPLC METHOD DEVELOPMENT AND VALIDATION FOR DETERMINATION AND ESTIMATION OF LAMIVUDINE AND TENOFOVIR DRUG WITH ITS BULK FORM AND TABLET FORMULATION - Manasa Kola (World Journal of Pharmaceutical Sciences, 2024)
A straight forward and robust technique was devised to simultaneously estimate the concentrations of Lamivudine and Tenofovir in tablet dose form. The chromatogram was passed through an Inertsil C18 150 mm (4.6 x 150mm, 5μm) Mobile phase that included a Buffer (Ammonium Acetate) consisting of 90% Methanol. 10% of the buffer was pushed through the column at a flux rate of 1.2 ml/min. Thermal condition was regulated at 26°C. The selected optimised wavelength was 245.0 nm. The observed retention times for Lamivudine and Tenofovir were 2.247 minutes and 2.879 minutes, respectively. The relative standard deviation (RSD) obtained for Lamivudine and Tenofovir were 0.5 and 0.7 correspondingly. %The recoveries achieved for Lamivudine and Tenofovir were 101.07% and 99.98% respectively. The linear optical density (LOD) and limit of quantification (LOQ) values derived from the regression equations of Lamivudine and Tenofovir were 0.18, 0.19, and 0.54, 0.56 correspondingly. There are two regression equations for Lamivudine: y = 8523.9x + 11099 and y = 12735x + 2600.A reduction in retention times and a corresponding drop in run time made the devised approach easy and cost-effective for use in routine quality control tests in industries